Type of anesthesia used for caesarean delivery in two hospitals of the Małopolska Province (Poland) - Barnaś, Edyta; Kołpa, Małgorzata; Wolak, Dorota; Gawlik, Bogumił (European Journal of Clinical and Experimental Medicine, 2016)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Background. Recent years have witnessed an increase in the number of elective caesarean deliveries. Conduction anesthesia, mainly spinal, is the type of anesthesia most frequently used for caesarean delivery. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Purpose. The survey aimed to conduct comparative analysis of anesthesia types used for caesarean deliveries in two selected hospitals of the Małopolska Province (county of Tarnow), Poland, in 2014. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Anesthetic records for 1097 caesarean deliveries were analyzed (including: patients’ age, anthropometric data and ASA physical status score, type of performed anesthesia, pre-anesthetic fluids, type of spinal needles and a drop in arterial blood pressure after the blockade). The parametric chi-squared test and the nonparametric Kruskal- Wallis and U-Mann Whitney tests were used to analyze the data collated. The level of significance was accepted at < 0.05. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The mean age of females subjected to caesarean section equaled 32.3±5.42 and their mean ASA score was 1.02±0.15. On balance, conduction spinal anesthesia was the most frequently selected anesthetic to prevent pain, and in group B, 26G standard spinal needles and a greater dose of Marcaine were far more routinely used. The HAES solution was in group B the most frequently selected method of hydration. It was disclosed that hydration with the HAES colloidal solutions before the surgical intervention resulted in a smaller drop in ABP after anesthesia. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Spinal anesthesia was the most frequently selected method of anesthesia for caesarean delivery. The ABP drop was the most prevailing complication resulting from conduction anesthesia for caesarean delivery. Hydration with colloid and crystalloid fluids was implemented as a preventive measure against hypotension.